The Role of Social Support and Work Engagement in Enhancing Job Performance among Secondary School Teachers: A Quantitative Study in Lahore District - Rasheed, Laila (Journal of Policy Options, 2020)
The focus of this study is to assess the importance and necessity of social support and work engagement in enhancing the job performance of secondary school teachers. Given the critical role that teachers play in shaping the educational system and influencing student outcomes, understanding the factors that contribute to their effectiveness is paramount. By examining the relationship between social support, work engagement, and job performance, the study aims to uncover insights into how support networks and professional engagement can positively impact the performance of secondary school teachers. Ultimately, the findings will shed light on the significance of social support in bolstering the performance of SSTs, thereby contributing to the improvement of the educational system as a whole. This quantitative study employed a survey method to gather data from 320 secondary school teachers in the Lahore district. The research instrument utilized was a questionnaire designed to assess social support, work engagement, and job performance among SSTs. Through statistical analysis, the study found that both social support and work engagement positively predicted the job performance of secondary school teachers. Additionally, the results indicated that social support significantly predicted work engagement among SSTs. These findings provide valuable insights into the importance of fostering supportive environments and promoting professional engagement among teachers to enhance their job performance. The implications of these findings for motivating and assisting teachers were also discussed, offering practical recommendations for improving teacher effectiveness and ultimately contributing to the overall quality of education.